Grain fiber-PVC (polyvinyl chloride) composite foamed sheet with surface co-extrusion layer and preparation method of grain fiber-PVC composite foamed sheet
By using technical means such as surface coextruded layer structure and rare earth composite stabilizer in the valley fiber-PVC composite foamed sheet, the problem of low bonding efficiency between rice husk and PVC material in the existing technology is solved, and the preparation of high-efficiency foamed sheet is achieved, and the performance and environmental protection of the sheet are improved.
Patent Information
- Application Number
- CN202411315749.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-03-04
AI Technical Summary
The prior art has failed to effectively combine rice husks with PVC materials to form efficient foamed sheets with surface coextrusion layers, resulting in waste of resources and environmental pollution.
The glutinous fiber-PVC composite foamed plate with a surface coextrusion layer is used. The intermediate foam layer and the surface coextrusion layer contain PVC resin and rice husk powder. Combined with rare earth composite stabilizer, foaming agent and foaming regulator, the plate density is controlled to be between 0.50-0.70g/cm3 to improve surface hardness and smoothness.
The efficient use of rice husks and PVC materials is achieved to form an efficient foamed plate with a surface coextrusion layer, which improves the mechanical properties, low temperature stability and environmental protection properties of the plate, and reduces resource waste and environmental pollution.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, in particular to the field of IPCB29D7, and more specifically to a grain fiber-PVC (polyvinyl chloride) composite foaming board with a surface co-extruded layer and a preparation method thereof. Background Art
[0002] For a long time, rice husks have been treated as waste, and even burned as fuel, with very limited utilization. This has caused waste of resources and pollution to the environment. Although people have been conducting extensive research on the comprehensive utilization of rice husks and have achieved some results, there are not many effective ways to form large-scale production and consume a large amount of rice husks in actual applications. PVC foam board or wood-plastic board is also called crust foam board. Its biggest advantages are anti-corrosion, moisture-proof, mildew-proof, heat-insulating, non-absorbent, drillable, sawable, planable, light in material, easy to construct, and inexpensive. How to efficiently utilize PVC and rice husks is the current research focus.
[0003] Chinese invention patent CN113683848A discloses a composition of a corn fiber imitation wood composite material for manufacturing door and window profiles, comprising: 50-60 weight % PVC resin, 4-8 weight % impact modifier, 1-5 weight % processing aid, 1-4 weight % lubricant, 8-10 weight % composite stabilizer, 12-17 weight % rice husk powder, 10-17 weight % calcium carbonate. In the invention, PVC as a polar material can be beneficial to oiling, varnishing, glazing or painting on the surface of the imitation wood; because the lignin contained in the rice husk is less (only about 5%), the imitation wood is not easy to fade or even will not fade under the influence of weather (sunlight, rain); rice husk and / or peanut shell as "active filler" provide sufficient processability for the imitation wood, which can be applied in multiple fields.
[0004] Chinese invention patent CN104015380A discloses a method for preparing environmentally friendly building boards, which involves the preparation of board base materials: after the plastic content of the raw materials is determined, thermoplastic plastic powder, plant fiber powder, and plastic additives are added as required, and then mixed, heated, stirred, and extruded to form board raw materials; board forming: the board raw materials are extruded into boards, and reinforcing nets and decorative films are sequentially attached to the surface of the boards, and after cooling and shaping, they are cut into finished boards of the required size. Domestic waste can be classified according to use, and each component in domestic waste can be fully utilized. Plastic substances and plant fiber substances can be directly used and converted into building board products that can be directly used without reclassification. However, the above invention does not involve foamed boards with co-extruded layers on both sides. Summary of the invention
[0005] The first aspect of the present invention provides a rice fiber-PVC composite foamed board with a surface co-extruded layer, comprising a middle foamed layer and a surface co-extruded layer, wherein both the middle foamed layer and the surface co-extruded layer comprise PVC resin and rice husk powder.
[0006] The surface co-extruded layer comprises an upper and a lower layer, and the middle foaming layer is located between the two surface co-extruded layers.
[0007] Preferably, the thickness of the middle foaming layer is 6-18 mm, and the thickness of the surface co-extrusion layer is 0.5-1.8 mm.
[0008] By weight percentage, the raw materials for preparing the middle foaming layer include: 10-20% rice husk powder, 15-25% first calcium carbonate, 2-10% foaming regulator, 1-5% rare earth composite stabilizer, 0.2-2% foaming agent, 0.1-2% auxiliary agent, and the first PVC resin making up the balance.
[0009] The average particle size of the first calcium carbonate is 2000-3000 meshes.
[0010] The viscosity of the first PVC resin (GB / T3401) is 85-95 mL / g, and the degree of polymerization is 850-750.
[0011] Preferably, the viscosity of the first PVC resin is 87-95 mL / g.
[0012] The foaming regulator includes an acrylic polymer.
[0013] Preferably, the foaming regulator includes HF-100 (Dongguan Hongfu New Materials Co., Ltd.) and ACR-401D (Dongying Ruikun Chemical Co., Ltd.), and the weight ratio of HF-100 to ACR-401D is 1:(0.8-1.8).
[0014] Preferably, the weight ratio of HF-100 to ACR-401D is 1:(0.8-1.1).
[0015] The foaming agent comprises AC foaming agent (azodicarbonamide) and NC foaming agent (soda), and the weight ratio of the AC foaming agent to the NC foaming agent is (0.2-0.7): (0.3-0.9).
[0016] Preferably, the weight ratio of the AC foaming agent to the NC foaming agent is 0.45:(0.3-0.9).
[0017] The weight ratio of the rare earth composite stabilizer, the foaming agent and the foaming regulator is (1-5): (0.5-1.6): (3-9).
[0018] Preferably, the weight ratio of the rare earth composite stabilizer, the foaming agent and the foaming regulator is 2:(0.5-1.6):(3-9).
[0019] The foaming regulator includes HF-100 (Dongguan Hongfu New Materials Co., Ltd.) and ACR-401D (Dongying Ruikun Chemical Co., Ltd.), and the weight ratio of HF-100 to ACR-401D is 1: (0.8-1.8), which can effectively reduce the plasticizing temperature, promote the plasticizing effect, improve the plasticizing efficiency, improve the melt strength, prevent melt fracture, and significantly improve the surface smoothness of the product. During the extrusion process, the foaming regulator is entangled with the PVC macromolecule in the form of molecules to form a network structure, which can not only promote the plasticization of PVC, but also significantly improve the strength and ductility of the foaming melt, so that the expansion of the foaming melt is in a stable and controllable state, and a valley fiber / PVC composite foamed board with uniform and fine pore structure and good independence is obtained. Due to the core-shell structure and network structure formed by ACR-401D and HF-100, the impact strength of the product at room temperature and low temperature is improved. At the same time, with the combination of specific foaming agents and lubricants, the board density can be controlled at 0.50-0.70g / cm 3 .
[0020] In the production process of PVC foamed boards, in order to fully plasticize the material, the temperature of the material is relatively high; and the cross-section of the board mold is wide and the flow channel is long, especially the shaping section of the crust foamed board mold is relatively long; in addition, the foaming agent also generates decomposition heat during the decomposition process. These factors require that the stabilizer must have sufficient thermal stability to ensure product quality and long-term stable production. The prior art usually uses lead-based composite stabilizers, in which metal salts of lead oxide and stearic acid have an activation effect on the foaming agent, which will widen the decomposition temperature of the foaming agent. Although the foaming temperature is reduced, attention should be paid to the stability of the molten material leaving the die to avoid local sudden and bubbling phenomena. However, lead-based composite stabilizers and calcium-zinc composite stabilizers are not conducive to improving the environmental protection of the material. The applicant has found that the addition of rare earth composite stabilizers not only has the function of environmental protection, but also has the functions of coupling, enhancement and brightness in PVC materials. In addition, rare earth composite stabilizers can also adjust the decomposition temperature of the foaming agent to achieve toughening and capacity expansion. If the amount of stabilizer added is too much or too little, the decomposition temperature of the foaming agent is too low or too high, which is not conducive to foaming. If the stabilizer is added too much or the melt temperature is too high, the foaming agent will decompose prematurely in the extruder, causing the foaming gas to escape from the feed hole and the vacuum hole. If the stabilizer is added too little or the operating temperature is too low, the foaming will be incomplete.
[0021] The basic requirements for preparing foamed products are: the molten material cannot foam before leaving the die lip; the decomposition temperature of the foaming agent should match the melting temperature range of PVC, and the residual amount of the foaming agent should be as small as possible, so as to ensure that the molten material is completely decomposed between leaving the die and the shaping die. The melt expands evenly after pressure release. Even in the case of high-speed extrusion, the expansion of the melt still maintains a gentle rate, and the surface cannot have local bubble aggregation and continuous blistering. The commonly used AC foaming agent (yellow) has many advantages. The ordinary AC foaming agent is a light yellow or orange crystalline powder with a decomposition temperature of about 180-200°C. Its biggest advantage is that the gas emission per unit mass is large, and the gas and decomposition residue released during decomposition are non-toxic and harmless, and have good compatibility with the melt; but its controllability is not strong, resulting in large viscosity fluctuations during the molding process, and poor bubble uniformity, affecting the surface quality of the board. However, its decomposition temperature after activation is too wide, and after leaving the die, it is very easy to produce local blistering, leaving scars on the surface of the product, and increasing the defective rate. It should also be pointed out that because the AC foaming agent contains an azo group, the decomposition residue will affect the detection of the environmental performance of the product, and more attention should be paid to export products. The applicant has found that the foaming agent is compounded with AC foaming agent and NC foaming agent, and the weight ratio of AC foaming agent and NC foaming agent is (0.2-0.7): (0.3-0.9), which can increase the extrusion rate and reduce the dimensional deviation of the product, and the surface hardness can reach a Shore D hardness of about 80. The fine characteristics and closed-cell structure of the bubbles formed by the compounding of the two are conducive to the formation of a dense and smooth surface. Under the condition of meeting the density requirements, the surface hardness can be increased to a Shore D hardness of about 80. Avoid the phenomenon of degradation and yellowing due to overheating of the core layer, and at the same time make the production stable and controllable. The molten material still maintains a gentle expansion rate after leaving the die, and the production stability and product shaping are good, which can effectively reduce the dimensional deviation of the product.
[0022] The weight ratio of the rare earth composite stabilizer, foaming agent and foaming regulator is (1-5): (0.5-1.6): (3-9). It can promote plasticization in the processing process and improve the mechanical properties of the material. Studies have found that during the foaming process of the material, the gas decomposed by the foaming agent forms bubbles in the melt. Among these bubbles, there is a tendency for small bubbles to expand to large bubbles. The size and number of bubbles are not only related to the amount of foaming agent added, but also to the strength of the polymer melt. If the strength is too low, the gas will easily escape after diffusing to the surface of the melt, and small bubbles will merge with each other to form large bubbles. The long molecular chain of the foaming regulator is entangled and adhered to the molecular chain of PVC to form a certain network structure. On the one hand, it promotes the plasticization of the material, and on the other hand, it improves the strength of the PVC melt, so that the bubble wall can withstand the pressure of the gas in the bubble during the foaming process, and will not break due to insufficient strength. The foaming regulator can make the product's bubbles small and numerous, and the bubble structure more uniform and reasonable, greatly reducing the density of the foam. Poor quality or insufficient amount of foaming regulator will lead to low strength of foam, broken bubbles or cross-bubbles. However, adding or replacing foaming regulator with a larger molecular weight will increase the density of the product due to excessive viscosity, which will prevent bubbles in the melt from expanding. The excessive viscosity of the melt will lead to poor fluidity, resulting in uneven discharge from the die, affecting the flatness of the board surface, and even causing fuzzy material failures in the die within a short production period, especially when producing boards with a thickness of less than 10 mm.
[0023] The raw materials for preparing the surface co-extrusion layer include, by weight percentage: 10-20% rice husk powder, 15-25% second calcium carbonate, 1-4% impact modifier, 1-5% light stabilizer, 1-6% toughening agent, 0.5-2% flow enhancer, 0.5-2% lubricant, 3-10% second auxiliary agent, and the balance is made up by second PVC resin.
[0024] The viscosity of the second PVC resin is 118-107 mL / g, and the degree of polymerization is 1100-1000.
[0025] The average particle size of the second calcium carbonate is 3000-4000 meshes.
[0026] Preferably, the first calcium carbonate and the second calcium carbonate are both activated calcium carbonate.
[0027] The rice husk powder of the surface co-extrusion layer and the middle foaming layer are both activated by a coupling agent.
[0028] The rice husk powder processing method comprises: firstly screening the rice husks, then washing, drying, crushing, secondary screening, sieving, the finished powder fineness is 40-60 mesh, and then packaging, bagging and short-term storage.
[0029] The water content of the rice husk powder should be controlled within 1.5-2.0%, and secondary drying treatment is required if necessary.
[0030] The rice husk powder activation treatment process includes: adding the treated rice powder into a high-speed mixer (with a heating device), heating to 80-100° C. while stirring at high speed, adding a coupling agent, continuing to stir to 110-130° C., and discharging the material from the pot into a cold mixing device to reduce the temperature to below 50° C. before packaging for later use. The packaging bag is a waterproof packaging.
[0031] The oil absorption of untreated rice powder and calcium carbonate surfaces is very poor, and the affinity and compatibility with the raw materials in the system are poor, which makes extrusion molding difficult. The present application found that the first calcium carbonate and the second calcium carbonate are both activated calcium carbonates, and the rice husk powder of the surface co-extrusion layer and the middle foaming layer are activated with a coupling agent, which effectively improves the dispersibility between the systems and increases the hardness and rigidity of the product surface.
[0032] The light stabilizers include UV-770 and UV-531.
[0033] Preferably, the weight ratio of UV-770 to UV-531 is 1:(0.8-1.5).
[0034] The light stabilizers include UV-770 and UV-531. On the basis of having better mechanical properties, the artificial aging test can reach the quality standard of 6000 hours, meeting the use requirements of exterior window profiles.
[0035] The weight ratio of the rice husk powder to the second PVC resin in the surface co-extrusion layer is 1:(8-12).
[0036] Preferably, the weight ratio of rice husk powder to the second PVC resin in the surface co-extrusion layer is 1:(8-10).
[0037] The weight ratio of the flow enhancer to the lubricant is 1:(0.8-1.5).
[0038] Preferably, the weight ratio of the flow enhancer to the lubricant is 1:(0.8-1.2).
[0039] The weight ratio of the impact modifier to the toughening agent is (2-3): (3-5).
[0040] Preferably, the weight ratio of the impact modifier to the toughening agent is 2.5:(3-5).
[0041] The physical properties of Gumuyuan formula materials are generally hard and brittle, especially under impact conditions at low temperatures, which limits their outdoor use, especially in northern China. The present application found that the weight ratio of the impact modifier to the toughening agent is (2-3): (3-5), which can improve the low-temperature stability and low-temperature impact resistance of the material.
[0042] Since a large amount of rice husk powder and calcium carbonate are added to the surface co-extrusion layer formula, the plasticization state of the raw material during the profile extrusion process is very poor, the fluidity of the raw material has resistance, the equipment produces a large torque, the main engine current is also very high, exceeding the rated standard value, causing great difficulties in the molding of the profile. The applicant has found that the weight ratio of the flow enhancer to the lubricant is 1: (0.8-1.5), which can improve the plasticization degree and fluid state of the raw material in the barrel, thereby improving the dimensional stability, foaming ratio and unit density of the material.
[0043] The second aspect of the present invention provides a method for preparing a grain fiber-PVC composite foamed board with a surface co-extrusion layer, comprising the following steps: mixing the surface co-extrusion layer raw material and the middle foaming layer raw material to prepare a mixture, and then extruding and molding by co-extrusion technology to obtain the mixture.
[0044] The method of mixing raw materials includes: accurately weighing the raw materials and feeding them in the order of process requirements; determining the time of adding the foaming agent according to the type of foaming agent used to reach the kneading end point; when the material temperature reaches 115-135°C, placing the material in a cold stirring pot to cool it down to 40-60°C.
[0045] The specific method of mixing raw materials can prevent agglomeration and premature decomposition of the foaming agent, which will affect the foaming ratio and avoid increasing the product density.
[0046] The extruder used for the co-extrusion has the following parameters: zone 1: 175-186°C, zone 2: 180-186°C, zone 3: 185-190°C, connector: 175-185°C, die head: 190-200°C, main machine current: 50-70A, screw speed: 14-22r / min.
[0047] Beneficial Effects
[0048] 1. The viscosity of the first PVC resin is 85-95mL / g, which can improve the plasticizing performance of processing and is used to produce large-scale boards. The foaming ratio and board thickness are easy to control, and the product qualification rate is high.
[0049] 2. The foaming regulator includes HF-100 (Dongguan Hongfu New Materials Co., Ltd.) and ACR-401D (Dongying Ruikun Chemical Co., Ltd.), the weight ratio of HF-100 to ACR-401D is 1: (0.8-1.8), which can effectively reduce the plasticizing temperature, promote the plasticizing effect, improve the plasticizing efficiency, increase the melt strength, prevent melt fracture, and significantly improve the surface smoothness of the product.
[0050] 3. Adding rare earth composite stabilizer not only has the function of environmental protection, but also has the functions of coupling, strengthening and brightening in PVC materials. In addition, rare earth composite stabilizer can also adjust the decomposition temperature of foaming agent to achieve the effect of toughening and capacity expansion.
[0051] 4. The foaming agent is a compound of AC foaming agent and NC foaming agent, and the weight ratio of AC foaming agent to NC foaming agent is (0.2-0.7): (0.3-0.9), which can increase the extrusion rate and reduce the dimensional deviation of the product, and the surface hardness can reach about 80 Shore D hardness.
[0052] 5. The weight ratio of rare earth composite stabilizer, foaming agent and foaming regulator is (1-5): (0.5-1.6): (3-9). It can promote plasticization in the processing process and improve the mechanical properties of the material.
[0053] 6. Both the first calcium carbonate and the second calcium carbonate are activated calcium carbonate, and the rice husk powder of the surface co-extrusion layer and the middle foaming layer are activated by a coupling agent, which effectively improves the dispersibility between the systems and increases the hardness and rigidity of the product surface.
[0054] 7. The light stabilizers include UV-770 and UV-531. On the basis of having better mechanical properties, the artificial aging test can reach the quality standard of 6000 hours, meeting the use requirements of exterior window profiles.
[0055] 8. The weight ratio of the impact modifier to the toughening agent is (2-3): (3-5), which can improve the low-temperature stability and low-temperature impact resistance of the material.
[0056] 9. The weight ratio of flow enhancer to lubricant is 1:(0.8-1.5), which can improve the plasticization degree and fluid state of the raw materials in the barrel, thereby improving the dimensional stability, foaming ratio and unit density of the material. DETAILED DESCRIPTION
[0057] Example 1
[0058] The invention discloses a grain fiber-PVC composite foaming board with a surface co-extruded layer, which consists of a 10mm thick middle foaming layer and a 1mm thick surface co-extruded layer.
[0059] The raw materials for preparing the intermediate foaming layer are as follows, by weight percentage, wherein:
[0060] Rare earth composite stabilizer 3%, model: 57-11-4, Shandong Desheng New Materials Co., Ltd.;
[0061] AC foaming agent (foaming agent) 0.5%, model: AC-9, Guangzhou Huike Chemical Co., Ltd.;
[0062] NC foaming agent (foaming agent) 0.6%, model: BTH-103, Guangdong Weilinna New Materials Co., Ltd.;
[0063] Oxidized polyethylene wax (first additive) 0.3%, model: S3815, Qihong (Shanghai) Investment Holding Co., Ltd.;
[0064] Low-density PE wax (first additive) 0.4%, model: QH-6A, Qihong (Shanghai) Investment Holding Co., Ltd.;
[0065] Foaming regulator 6%, model: HF-100, Dongguan Hongfu New Materials Co., Ltd.;
[0066] First calcium carbonate 18%, model: HX-2500, Jiangxi Guangyuan Chemical Co., Ltd.;
[0067] Rice husk powder 14%, model: 60-80 mesh, Shanghai Qingying Industrial Co., Ltd., activated;
[0068] The first PVC resin makes up the balance, model: SG-700, Xinjiang Zhongtai Chemical Co., Ltd.
[0069] The raw materials for preparing the surface co-extrusion layer are as follows, by weight percentage:
[0070] Impact modifier 2.5%, model: LS-55, Shandong Ruifeng Chemical Company;
[0071] Flow enhancer 1.2%, model: ACR125A, Shandong Huaxing Chemical Company;
[0072] Lubricant 1.2%, model: 0W-0539, Nanjing Tianshi Material Technology;
[0073] Stabilizer (second auxiliary agent) 4%, model: calcium zinc system, Changzhou Aiteen Company;
[0074] Rice husk powder 7%, size: 60-80 mesh, produced by Qingying Company;
[0075] Second calcium carbonate 12%, model: 4000 mesh, Jiangxi Guangyuan Chemical;
[0076] Toughening agent 4%, model: WD-P1, Shandong Riko Chemical;
[0077] Antioxidant (second auxiliary agent) 0.4%, model: 1010, Changzhou Aiteen Company;
[0078] UV-531 (light stabilizer) 0.2%, Tianjin Lianlong New Materials Co., Ltd.;
[0079] UV-770 (light stabilizer) 0.2%, Tianjin Lianlong New Materials Co., Ltd.;
[0080] The second PVC resin makes up the balance, model: S1000, Shanghai Chlor-Alkali Co., Ltd.
[0081] A method for preparing a grain fiber-PVC composite foaming board with a surface co-extrusion layer comprises the following steps: respectively mixing the raw materials of the surface co-extrusion layer and the raw materials of the middle foaming layer to prepare a mixture, and then adopting the co-extrusion technology to extrude and shape the mixture.
[0082] The parameters of the extruder used in the co-extrusion are: zone 1: 180°C, zone 2: 183°C, zone 3: 188°C, connector: 180°C, die head: 195°C, main machine current: 60A, screw speed: 18r / min.
[0083] Comparative Example 1
[0084] Specific implementation method The same as Example 1, except that the first PVC resin in Comparative Example 1, model: SG-5, Xinjiang Zhongtai Chemical Co., Ltd. A lead salt stabilizer (customized by Tianyu) is used to replace the rare earth composite stabilizer.
[0085] Performance Testing Methods
[0086] The composite materials prepared in Example 1 and Comparative Example 1 were tested for performance. The test data of Example 1 are listed in Table 1. Comparative Example 1 had poor foaming effect and was not tested.
[0087] Performance test data
[0088] Table 1
[0089]
Claims
1. A grain fiber-PVC composite foamed board with a surface co-extruded layer, characterized in that: The invention comprises a middle foaming layer and a surface co-extrusion layer, wherein both the middle foaming layer and the surface co-extrusion layer comprise PVC resin and rice husk powder.
2. The grain fiber-PVC composite foamed board with a surface co-extruded layer according to claim 1, characterized in that: By weight percentage, the raw materials for preparing the middle foaming layer include: 10-20% rice husk powder, 15-25% first calcium carbonate, 2-10% foaming regulator, 1-5% rare earth composite stabilizer, 0.2-2% foaming agent, 0.1-2% first auxiliary agent, and the first PVC resin making up the balance.
3. The grain fiber-PVC composite foamed board with a surface co-extruded layer according to claim 2, characterized in that: The viscosity of the first PVC resin is 95-87 mL / g, and the degree of polymerization is 850-750.
4. The grain fiber-PVC composite foamed board with a surface co-extruded layer according to claim 3, characterized in that: The foaming agent comprises an AC foaming agent and a NC foaming agent, and the weight ratio of the AC foaming agent to the NC foaming agent is (0.2-0.7):(0.3-0.9).
5. The grain fiber-PVC composite foamed board with a surface co-extruded layer according to claim 4, characterized in that: The weight ratio of the rare earth composite stabilizer, the foaming agent and the foaming regulator is (1-5): (0.5-1.6): (3-9).
6. The grain fiber-PVC composite foamed board with a surface co-extruded layer according to claim 1 or 5, characterized in that: The raw materials for preparing the surface co-extrusion layer include, by weight percentage: 10-20% rice husk powder, 15-25% second calcium carbonate, 1-4% impact modifier, 1-5% light stabilizer, 1-6% toughening agent, 0.5-2% flow reinforcing agent, 0.5-2% lubricant, 3-10% second auxiliary agent, and the balance is made up by second PVC resin; the viscosity of the second PVC resin is 118-107mL / g, and the degree of polymerization is 1100-1000.
7. The grain fiber-PVC composite foamed board with a surface co-extruded layer according to claim 6, characterized in that: The rice husk powder is activated by using a coupling agent.
8. The grain fiber-PVC composite foamed board with a surface co-extruded layer according to claim 7, characterized in that: The weight ratio of the rice husk powder to the second PVC resin in the surface co-extrusion layer is 1:(8-12).
9. The grain fiber-PVC composite foamed board with a surface co-extruded layer according to claim 8, characterized in that: The weight ratio of the impact modifier to the toughening agent is (2-3): (3-5).
10. A method for preparing a grain fiber-PVC composite foamed board having a surface co-extruded layer according to any one of claims 7 to 9, characterized in that: The following steps are involved: The raw materials of the surface co-extrusion layer and the raw materials of the middle foaming layer are mixed separately to prepare a mixed material, and then a co-extrusion technology is adopted to extrude and shape the mixed material.
Citation Information
Patent Citations
Preparation method of environment-friendly plate of building
CN104015380A
Grain fiber wood-like composite material and manufacturing method thereof
CN113683848A
Three-layer coextruded PVC (polyvinylchloride) wood-plastic composite foam board and preparation method thereof
CN102922838A
Composite plastic formwork and preparation method thereof
CN103213362A
High rigidity and low density PVC (polyvinyl chloride) wood plastic foaming board and preparation method thereof
CN104130529A